2016
DOI: 10.1038/ncomms12125
|View full text |Cite
|
Sign up to set email alerts
|

NEDDylation promotes stress granule assembly

Abstract: Stress granules (SGs) harbour translationally stalled messenger ribonucleoproteins and play important roles in regulating gene expression and cell fate. Here we show that neddylation promotes SG assembly in response to arsenite-induced oxidative stress. Inhibition or depletion of key components of the neddylation machinery concomitantly inhibits stress-induced polysome disassembly and SG assembly. Affinity purification and subsequent mass-spectrometric analysis of Nedd8-conjugated proteins from translationally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 53 publications
4
68
0
Order By: Relevance
“…It has been suggested that G3BP has both antiviral and proviral activities by activating PKR (95,96) and suppressing P1234 translation (97), that it escorts the incoming genomic RNA to the plasma membrane (37), and that it regulates the switch from translation to transcription of genomic RNA (91). G3BP1 is the target for several posttranslational modifications (e.g., phosphorylation, ADP ribosylation, acetylation, methylation, NEDDylation, and ubiquitylation) that regulate its endonuclease activity and its participation in the formation of stress granules and other protein complexes (94,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). The presence or absence and the location of these modifications likely also play a regulatory role in interaction with nsP3 and genomic RNA for initiation of alphavirus replication.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that G3BP has both antiviral and proviral activities by activating PKR (95,96) and suppressing P1234 translation (97), that it escorts the incoming genomic RNA to the plasma membrane (37), and that it regulates the switch from translation to transcription of genomic RNA (91). G3BP1 is the target for several posttranslational modifications (e.g., phosphorylation, ADP ribosylation, acetylation, methylation, NEDDylation, and ubiquitylation) that regulate its endonuclease activity and its participation in the formation of stress granules and other protein complexes (94,(98)(99)(100)(101)(102)(103)(104)(105)(106)(107). The presence or absence and the location of these modifications likely also play a regulatory role in interaction with nsP3 and genomic RNA for initiation of alphavirus replication.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results also clearly establish that acute inhibition of active protein ubiquitylation or neddylation does not directly impact SG formation or dissolution despite the large impact on overall protein ubiquitylation. Previous studies demonstrated that long-term (18hr) NAE inhibition or knockdown of neddylation components inhibits SG formation 20, 21 . Near complete NAE inhibition using the N8-E1i takes place on minute timescales when added to mammalian cells 45 .…”
Section: Discussionmentioning
confidence: 99%
“…NEDD8 (neural precursor cell‐expressed developmentally downregulated protein 8) is a small, ubiquitin‐like protein that covalently attaches to protein substrates in a manner similar to ubiquitination, known as neddylation. Neddylation of serine/arginine (SR)‐rich splicing factor 3 (SRSF3), an SG regulator, is necessary for SG formation (Jayabalan et al, 2016). Reversible protein acetylation is another important protein PTM modulated by histone acetylases and histone deacetylases.…”
Section: Stress Granule Formation and Regulationmentioning
confidence: 99%